2013
DOI: 10.1179/1743294412y.0000000078
|View full text |Cite
|
Sign up to set email alerts
|

Ceramic coatings in ancient times: high technology surface modification technologies

Abstract: Ceramic coatings on ancient pottery, in particular black gloss, transparent glaze (first alkali based and then lead based) and opaque glaze (enamel) up to the lustre decoration, can be considered as the top technological skill of ancient ceramists. Indeed, their production demands the ceramist a thorough knowledge of pyrotechnology, including the ability to strictly control furnace atmosphere conditions. Several papers have dealt with the study of ceramic coatings, aiming to reconstruct the production technolo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…These TBC materials must have sufficient thickness, low porosity, low surface roughness and high hardness, not only to withstand the load bearing alloy and coating surface, but also must give protection against high-temperature corrosion and erosion. Ceramic materials are the ideal materials for thermal barrier coating applications due to high thermal stability, high hardness and low thermal conductivity [3][4][5]. The thermal barrier coatings are porous materials, which have high value of porosities, and hence have many local micro-cracks or through pores, and are coated on a rough surface [6,7].…”
Section: Introductionmentioning
confidence: 99%
“…These TBC materials must have sufficient thickness, low porosity, low surface roughness and high hardness, not only to withstand the load bearing alloy and coating surface, but also must give protection against high-temperature corrosion and erosion. Ceramic materials are the ideal materials for thermal barrier coating applications due to high thermal stability, high hardness and low thermal conductivity [3][4][5]. The thermal barrier coatings are porous materials, which have high value of porosities, and hence have many local micro-cracks or through pores, and are coated on a rough surface [6,7].…”
Section: Introductionmentioning
confidence: 99%
“…For effective applications at high temperature, these coatings should have sufficient thickness, low porosity with good surface finish, high hardness than substrate material. Ceramic materials are the ideal materials for these coatings due to high thermal stability, high hardness and low thermal conductivity [1,9,10]. Several studies have shown Cr 3 C 2 –NiCr coatings have high corrosion and erosion resistance at high temperatures upto 900°C.…”
Section: Introductionmentioning
confidence: 99%
“…GCCs are employed in high-temperature-, thermal shock-, corrosion-, and abrasion-resistant applications, such as cookware, boilers, and architectural applications, owing to the amorphous and at least one embedded crystalline phase nature. These coatings can be applied on steel, copper, cast iron, and aluminium alloy substrates using a variety of processes, such as dipping, wet/electrostatic spraying, and electrophoretic coating [1][2][3].…”
Section: Introductionmentioning
confidence: 99%